PECULIARITIES OF LEGAL REGULATION OF THE CHILDREN MAINTENANCE UNDER THE EU LEGISLATION - Lypets, Lyudmyla (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose is to make comprehensive analysis of the paternal obligation to maintain the children and its role in science and practice of the international private law, making proposals on improvement of the effective legislation of Ukraine in the children maintenance field based on the experience of the EU countries. Methods: are philosophic and world-viewed, general and special scientific methods and approaches that secure objective analysis of the subject. Results: It is more effective to implement collection of the children alimony at the administrative level (like in Great Britain and Latvia), so we propose to create in Ukraine specialized institution empowered to calculate the alimony, search for the debtors, to collect the alimony and apply the appropriate influence on the debtors. Based on the positive experience of some developed countries of the EU we propose to determine in the Family Code of Ukraine the differentiation of the alimony amount to be collected as the fixed cash amount, as follows: from birth to 6 years old (preschool age), from 6 to 12 years old, 12 to 18 years old (by reaching majority). We propose to include the point on consideration of the debtor’s income from lease of real property to the List of Types of Incomes Used during Granting the Alimony Amount. Discussion: This article is devoted to peculiarities of the paternal maintenance in the EU countries that is not typical for Ukraine. The author analyzed special features of work of the Guarantee Fund of Costs for Children Maintenance in Latvia, researched a mechanism of the state maintenance system in Great Britain and Germany. The author also considered the legislation of the Member States of the Organisation for Economic Co-operation and Development (OECD) which have a system of state agencies on the child maintenance that use strict mathematical formulas to calculate the alimony, etc.